The boundary conditions for regulation: Welfare systems, state traditions, and the varied governance of work safety in Europe. Issue 1 (27th January 2020) - Rothstein, Henry; Paul, Regine; Demeritt, David
Abstract : Studies of the relationship between the welfare and regulatory state have hitherto either focused on the latter displacing the former, or presented regulation as an alternative means for achieving welfare goals. Little is known, however, about their varied mutual interactions. This article addresses that gap by examining the coevolution of workers' compensation and occupational safety regulation in Germany, France, the United Kingdom, and the Netherlands. Drawing on an extensive international analysis of primary documents, secondary literature, and interviews with regulator, insurance, business, and labor representatives, the article identifies strikingly varied but stable national preferences for: (a) the use of financial versus regulatory instruments and (b) the allocation of regulatory responsibilities between state and nonstate actors. The article presents a novel explanation of that variation as dependent on the relative coherence of interactions between the particular cost‐control logics of welfare provision and wider norms and traditions of state action in each country.